Conducting psychological assessment : a guide for practitioners - Wright, A. Jordan (Hoboken, New Jersey : John Wiley & Son, Inc., 2021)
It has been about ten years since the original edition of Conducting Psychological Assessment came out, and since then it has been used consistently, especially within educational contexts, to train psychologists in the process of psychological assessment, especially related to integrating data and writing reports. The hypothesis testing model proposed in the original book has become the standard for ethical and rigorous comprehensive (multi-method) assessment.
PART I Conducting Psychological Assessment -- Introduction to Part I: The Hypothesis Testing Model -- Chapter 1 The Initial Clinical Assessment: Clinical Interviewing and Hypothesis Building -- Chapter 2 Selecting Tests -- Chapter 3 Testing -- Chapter 4 Integrating Data -- Chapter 5 Writing Reports -- Chapter 6 Providing Feedback -- PART II Case Studies in Psychological Assessment -- Introduction to Part II: CASE STUDIES IN PSYCHOLOGICAL ASSESSMENT -- Chapter 7 A Woman With Poor Attention -- Chapter 8 A Woman With Interpersonal Problems -- Chapter 9 A Young Man Who Steals -- Chapter 10 An Adolescent Girl With Test Anxiety -- Chapter 11 An Aggressive Boy -- Chapter 12 An Adolescent Girl With School Problems -- References -- Index.
Keywords: PERSONALITY ASSESSMENT